2012
DOI: 10.1289/ehp.1205327
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight, Head Circumference, and Prenatal Exposure to Acrylamide from Maternal Diet: The European Prospective Mother–Child Study (NewGeneris)

Abstract: Background: Acrylamide is a common dietary exposure that crosses the human placenta. It is classified as a probable human carcinogen, and developmental toxicity has been observed in rodents.Objectives: We examined the associations between prenatal exposure to acrylamide and birth outcomes in a prospective European mother–child study.Methods: Hemoglobin (Hb) adducts of acrylamide and its metabolite glycidamide were measured in cord blood (reflecting cumulated exposure in the last months of pregnancy) from 1,101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 28 publications
6
79
1
Order By: Relevance
“…Again, a highly significant correlation was observed between cord and maternal blood with regard to the Hb adducts of AA and also GA, for which the adduct ratio of cord to maternal blood was around 0.38. Similarly, in a study which included 1 101 cord blood samples and 172 maternal blood samples from Greece, Spain, England, Denmark and Norway (Pedersen et al, 2012), the median AA-Hb adduct levels in cord blood were approximately half of the levels in paired maternal blood. Hb adduct levels in cord blood were positively correlated with both maternal AA-Hb adduct (r = 0.95) and GA-Hb adducts (r = 0.94).…”
Section: Placental Transfermentioning
confidence: 93%
See 2 more Smart Citations
“…Again, a highly significant correlation was observed between cord and maternal blood with regard to the Hb adducts of AA and also GA, for which the adduct ratio of cord to maternal blood was around 0.38. Similarly, in a study which included 1 101 cord blood samples and 172 maternal blood samples from Greece, Spain, England, Denmark and Norway (Pedersen et al, 2012), the median AA-Hb adduct levels in cord blood were approximately half of the levels in paired maternal blood. Hb adduct levels in cord blood were positively correlated with both maternal AA-Hb adduct (r = 0.95) and GA-Hb adducts (r = 0.94).…”
Section: Placental Transfermentioning
confidence: 93%
“…Huang et al (2012) studied 51 AA-exposed workers and 34 controls to explore the effect of genetic polymorphisms of CYP2E1, mEH3, mEH4, GSTT1 and GSTM1 on AA and GA-Hb adduct levels. The results suggest that mEH4 and the combined genotypes of CYP2E1, GSTM1 and mEH4 may be associated with the formation of AAVal and GAVal (Huang et al, 2012) The effects of prenatal exposure to AA measured by determinations of AA-and GA-Hb adducts on birth weight and head circumference (Pedersen et al, 2012) is described in Section 7.4.2. In this study, which used cord blood samples from Greece, Spain, England, Denmark and Norway, it was observed that the median AA-Hb and GA-Hb adduct levels were higher in cord blood from children of mothers who smoked (n = 129) than in children of non-smokers (n = 972).…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also indications that the food-borne non-proteinogenic amino acid BMAA affects neurodevelopment (Karlsson et al, 2015). The same is true for acrylamide, a chemical generated from amino acid precursors during food processing (Duarte-Salles et al, 2013;Pedersen et al, 2012). However, more information regarding specificity is required; for example, acrylamide's effects on head circumference and brain weight may also be indirect consequences of toxicity.…”
Section: Examples Of Other Compounds Not Considered Herementioning
confidence: 99%
“…As a follow up of a study (54) that showed a negative association between a biological marker of acrylamide exposure and foetal growth (women from five European cohorts, including MoBa, total n=1,101), the association between calculated dietary acrylamide intake and foetal growth was examined in 50,561 women in MoBa. Calculated acrylamide intake showed strong correlation with haemoglobin-and glycidamide Hb-adducts in a subset of the participating women.…”
Section: Maternal Diet and Infant Size At Birthmentioning
confidence: 99%